Cosmic magnetic fields - Sánchez Almeida, J. (Jorge); Martínez González, María Jesus (Canary Islands Winter School of Astrophysics (Series), 2018)
An introduction to cosmic magnetic fields on a range of astrophysical and cosmological scales for young researchers and graduate students.